ANALISIS PERBEDAAN HARGA SAHAM SEBELUM DAN SAAT PANDEMI COVID-19 PADA PERUSAHAAN SUBSEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) (Fakultas Ekonomi dan Bisnis Universitas Faletehan, 2024)
Companies in the transportation and logistics sub-sector listed on the IDX will be the focus of this research. The outbreak of Covid-19 in Indonesia has had an impact on activities taking place in the capital market. The researcher will cite the following problem formulation whether there was a change in stock prices before and during Covid-19 in Indonesia in the transportation and logistics subsector companies listed on the IDX.The purpose of this study is to understand the differences in stock prices for the Indonesian transportation and logistics sector before and during Covid-19. The method used in this research is a type of quantitative research with comparative methods. The sample used in this study consisted of 31 companies, taken using purposive sampling. Data was processed using the Paired sample t test. The results of this discussion show that there were significant differences in stock prices before and during the Covid-19 pandemic in transportation and logistics subsector companies, so that the HO hypothesis was rejected and HI was accepted. -19 in Indonesia the stock price was recorded higher than before the Covid-19 pandemic was announced in Indonesia on May 2 2020.